Host Innate Immunity Against Hepatitis Viruses and Viral Immune Evasion - Xu, Chonghui; Chen, Jizheng; Chen, Xinwen (Frontiers in Microbiology, 2021)
Hepatitis viruses are primary causative agents of hepatitis and represent a major source of public health problems in the world. The host innate immune system forms the first line of defense against hepatitis viruses. Hepatitis viruses are sensed by specific pathogen recognition receptors (PRRs) that subsequently trigger the innate immune response and interferon (IFN) production. However, hepatitis viruses evade host immune surveillance via multiple strategies, which help compromise the innate immune response and create a favorable environment for viral replication. Therefore, this article reviews published findings regarding host innate immune sensing and response against hepatitis viruses. Furthermore, we also focus on how hepatitis viruses abrogate the antiviral effects of the host innate immune system.